2000
DOI: 10.1097/00044067-200008000-00009
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Ventilator Management Strategies: Experiences of Two Hospitals

Abstract: Historically, negative clinical and economic outcomes have been associated with patients who need long-term mechanical ventilation. Institutions and clinicians charged with the care of these patients are understandably interested in exploring clinical strategies that assure positive outcomes. This article describes the evidence base for clinical pathways, weaning teams, protocols, and care-managed approaches. In addition, the article describes how different elements of system initiatives designed for a univers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2000
2000
2013
2013

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 22 publications
0
7
0
Order By: Relevance
“…A number of studies have demonstrated that a standardized approach to mechanical ventilation weaning can shorten its duration. These standardized approaches may consist of weaning teams, weaning protocols, outcome management and clinical pathways (Burns & Dempsey 2000). However, Burns and Dempsey (2000) note that not all of these strategies may improve clinical outcomes, although they may improve the economic ones.…”
Section: Resultsmentioning
confidence: 99%
“…A number of studies have demonstrated that a standardized approach to mechanical ventilation weaning can shorten its duration. These standardized approaches may consist of weaning teams, weaning protocols, outcome management and clinical pathways (Burns & Dempsey 2000). However, Burns and Dempsey (2000) note that not all of these strategies may improve clinical outcomes, although they may improve the economic ones.…”
Section: Resultsmentioning
confidence: 99%
“…36,37 threshold was also practical from a process perspective (it prevented unnecessary enrollment of patients who may be quickly weaned) and early enough in the program to ensure that early assessment and appropriate interventions were initiated. As described extensively elsewhere, [41][42][43][44] advanced practice nurses (APNs) trained in the use of the BWAP who consistently scored the factors accurately by using standard definitions (Table 2) albumin/prealbumin may be used in conjunction with provision of feeding. In patients without available nutrition markers, an assessment of whether the patient is receiving what has been ordered is used in conjunction with absorption.…”
Section: Long-term Mechanical Ventilation Initiativementioning
confidence: 99%
“…Twenty publications evaluating cardiovascular clinical pathways were included in the study sample [15–34]. The relative number (%) of publications included in the study sample varied between 5% and 16% in the following domains: (1) respiratory diseases, therapy and thoracic surgery [28,35–51]; (2) gastrointestinal surgery, endoscopic surgery and diseases [52–70]; (3) orthopedic surgery and multiple trauma [71–83]; (4) oncological diseases and surgery [84–92]; (5) neurological trauma, disorders, diseases and pain management [93–100]; (6) vascular surgery [15,19,101–105]; and (7) gynaecological diseases, surgery and maternity care [106–111].…”
Section: Resultsmentioning
confidence: 99%
“…Twenty publications evaluating cardiovascular clinical pathways were included in the study sample [15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34]. The relative number (%) of publications included in the study sample varied between 5% and 16% in the following domains: (1) respiratory diseases, therapy and thoracic surgery [28,[35][36][37][38][39][40][41][42][43][44][45][46][47][48][49][50][51]; (2) gastrointestinal surgery, endoscopic Table 1 The evaluation items used to assess the methodological quality of the studies investigated Was a power analysis performed?…”
Section: Disease Treatmentsmentioning
confidence: 99%